Impact of teacher-student writing conferences on frequency and accuracy of using cohesive devices in EFL students’ writing - Abdullah Rajab Alfalagg (Asian-Pacific Journal of Second and Foreign Language Education, 2020)
Abstract While the bulk of feedback studies have focused on written corrective feedback, oral feedback in teacher-student writing conferences in EFL context has been underexplored. This article investigated teacher oral feedback based on the tenets of sociocultural theory. It examined the impact of teacher-student writing conferences on students’ accuracy and frequency of cohesive devices employment. The study followed a quasi-experimental design with a pre-test, intervention and post-test. Data were collected from an intensive writing course for intermediate students at the college level. Based on guided-free writing prompts, the students had to write argumentative paragraphs of about 150–180 words followed by individual conference sessions to offer them oral feedback. The findings showed that oral feedback in writing conferences statistically impacted the students’ writing performance with huge effect size (Cohen’s d = 2.19). Moreover, the results demonstrated empirical evidence that writing conferences positively impacted the students’ frequency of employing referential markers (t value = − 3.011; p = 0.006 < 0.05) and conjunctions (t value = − 2.200; p = 0.039 < 0.05). Further, oral feedback statistically impacted the students’ accuracy of utilizing referential markers (t value = − 6.874; p = 0.000 < 0.05) and conjunctions (t value = − 7.253; p = 0.000 < 0.05). Writing conferences provided mediated learning experience for the students. The oral feedback assisted the students to decrease the overuse of the first, second person pronouns and the definite article ‘the’ with generic meaning in their writing. Instead, they depended on noun phrases and the third person pronouns which contributed to the text overall cohesion by creating explicit chains of references to the antecedents within the textual environment. Also, oral feedback helped the students to use conjunctions appropriately and accurately, so their texts were written densely cohesive. Pedagogical implications were discussed at the end of the article.